SOME RESULTS OF THE PHOTOMETRY OF GEO OBJECTS - Sukhov, P. P.; Movchan, A. I.; Koshkin, N. I.; Korniychuk, L. V.; Strakhova, S. L.; Epishev, V. P. (Одеські астрономічні публікації, 2017)
Odessa Astronomical Observatory participated in the photometric observations of the GEO objects from June to September 2004. The photometric observations of the GEO objects were carried out at Observatory Station in Mayaky. For the observations 50 cm telescope Cassegrain was used. During the observations 7 light curves was obtained.